The Impact of Religion on the Space of Competition: The Dutch Case - Pellikaan, Huib (Politics and religion, 2010)
The political practice of consociational democracies to take religion off the political agenda has led to the idea that religious issues only play a marginal role in the left-right ideological framework. This study demonstrates that religion has more than a marginal effect on the left-right placement of parties and thus on the space of competition. The analysis shows that voters for secular parties and voters for religious parties have different motives and beliefs on which they base the orderings of parties on the left-right scale. In other words, each group of voters defines its own left-right scale. These different left-right scales are individually single-peaked but there is no collective transitivity of orderings of parties. The intransitivity is a clear violation of Downs' condition for placing all parties on a single line in a manner agreed upon by all voters. Instead of having one left-right dimension as some sort of "super issue," there are at least two left-right scales, one for voters for secular parties and one for voters for religious parties.